Analisis Persepsi Masyarakat Pangkal Pinang Terhadap Manfaat dan Risiko Partisipasi Dalam Tabungan Perumahan Rakyat (TAPERA) - Nurul Khotimah; Amira Nabila Putri; Ade Riatati (Dinasti Research, 2024)
This research analyzes the public perception in Pangkalpinang City towards the Public Housing Savings Program (TAPERA) launched by the government to provide affordable housing financing solutions. Through the empirical juridical method, data was collected through interviews and questionnaires from respondents consisting of civil servants and the general public. The results show that TAPERA is seen as a program that can help people own a house at a lower cost. However, there are concerns regarding the management of funds, the risk of corruption, and the lack of clear information about the program. The findings highlight the importance of transparency, better socialization and accountability in the implementation of TAPERA to increase public trust and participation.